Nanoimprint photoresist with high mechanical strength and high resolution and ink-jet printing method thereof

By using a combination of double bond-containing rigid monomers, thiol-containing rigid compounds, photoinitiators and organic solvents in nanoimprinting photoresist, the compatibility problems of inkjet printing and nanoimprinting technology are solved, and nanoimprinting photoresist with high mechanical strength and high resolution is achieved, enhancing the application value of nanoimprinting technology.

CN119556529AActive Publication Date: 2025-03-04UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202510103977.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-04
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The prior art has challenges in compatibility between inkjet printing and nanoimprinting technologies, including the viscosity, curing speed and precise control of photoresist, making it difficult to develop nanoimprinting photoresist with high mechanical strength and high resolution.

Method used

Using a combination of double bond-containing rigid monomers, thiol-containing rigid compounds, photoinitiators and organic solvents, nanoimprinted photoresist with rapid curing, antioxidant polymerization, high mechanical strength and high resolution were prepared through inkjet printing and ultraviolet curing technology.

Benefits of technology

The rapid inkjet printing and curing of photoresist with low viscosity at room temperature is achieved, ensuring high resolution and stability of the pattern, avoiding mold residues, and improving the compatibility and application value of nanoimprinting technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119556529A_ABST
    Figure CN119556529A_ABST
Patent Text Reader

Abstract

The invention discloses a nanoimprint photoresist with high mechanical strength and high resolution and an ink-jet printing method of the nanoimprint photoresist. The nanoimprint photoresist is mainly designed for compatibility of ink-jet printing and nanoimprint technologies and high-precision manufacturing in the semiconductor field, after screening and blending, photoresist liquid drops can be distributed by an ink-jet printing head according to needs, required patterns can be rapidly printed, and the yield of the nanoimprint photoresist is improved. And finally, exposure is carried out through a nanoimprint lithography machine to realize 50 nm high-resolution imprint. Compared with the nanoimprint photoresist in the prior art, the nanoimprint photoresist disclosed by the invention has the advantages of rapid ink-jet printing, high curing rate, excellent anti-oxygen polymerization inhibition performance, high mechanical strength, high resolution, easiness in demolding and the like. The invention aims to improve the operability and the reliability of the nanoimprint photoresist in practical application, and has potential application prospects in the high-precision manufacturing fields such as advanced semiconductor manufacturing processes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanoimprinting, and in particular relates to a nanoimprinting photoresist with high mechanical strength and high resolution and an inkjet printing method thereof. Background Art

[0002] Nanoimprint lithography (NIL) is an advanced micro-nano manufacturing process that can repeatedly replicate the structure on the mold to the target substrate surface in proportion. After more than 20 years of development, NIL technology has been proven to be able to efficiently and cost-effectively replicate nano features less than 10 nm, and has gradually become a powerful alternative to traditional high-end lithography technologies such as ion beam etching, electron beam lithography and extreme ultraviolet lithography.

[0003] According to different material and process requirements, nanoimprint technology is mainly divided into thermal nanoimprint and ultraviolet nanoimprint (UV-NIL). Compared with thermal nanoimprint, UV-NIL technology is favored in the industry because it does not require high temperature and high pressure and can be completed quickly at room temperature and low pressure. Among UV-NIL technologies, inkjet UV-NIL is regarded as one of the technologies with the most commercial prospects. Through inkjet printing technology, the pre-polymerized liquid of nanoimprint photoresist can be quickly and accurately distributed on the wafer surface according to the designed circuit pattern. However, the compatibility between inkjet printing technology and nanoimprint technology is facing some challenges, such as the viscosity of the photoresist, the curing speed, and the precise control of the inkjet process, which need to be solved by continuously optimizing the materials and process parameters. The integration of inkjet printing technology and nanoimprint technology requires not only precise technical deployment, but also the development of high-performance photoresist materials for specific applications to ensure the maximum synergy between the two. For example, in the field of advanced semiconductor manufacturing, in order to ensure the high resolution and stability of the final imprinted pattern, nanoimprint photoresist must have the characteristics of low viscosity, fast curing, no residue, anti-oxidation inhibition, good mechanical strength and high resolution.

[0004] Therefore, developing a nanoimprint photoresist suitable for inkjet printing with high mechanical strength and high resolution not only has important theoretical significance, but also has potential application value in promoting the practical application and industrialization of nanoimprint technology. Summary of the invention

[0005] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide a nanoimprint photoresist with high mechanical strength and high resolution and an inkjet printing method thereof. The nanoimprint photoresist prepared by the present invention has the characteristics of fast inkjet printing, fast curing rate, anti-oxidation inhibition, high mechanical strength, high resolution, easy demoulding, etc.

[0006] The nanoimprint photoresist with high mechanical strength and high resolution of the present invention comprises the following raw materials in terms of mass percentage:

[0007] 50 wt%~95 wt% of a rigid monomer containing a double bond, 0 wt%~20 wt% of a rigid compound containing a thiol group, 1 wt%~20 wt% of a photoinitiator, and 0 wt%~20 wt% of an organic solvent.

[0008] Further preferably, the rigid monomer containing a double bond is 80 wt% to 95 wt%, the rigid compound containing a thiol group is 1 wt% to 10 wt%, the photoinitiator is 1 wt% to 10 wt%, and the organic solvent is 0 wt% to 15 wt%.

[0009] More preferably, the rigid monomer containing a double bond accounts for 85 wt% to 95 wt%, the rigid compound containing a thiol group accounts for 1 wt% to 5 wt%, the photoinitiator accounts for 1 wt% to 5 wt%, and the organic solvent accounts for 0 wt% to 1 wt%.

[0010] The double bond-containing rigid monomer is selected from one of the following substances or a mixture thereof: styrene, divinylbenzene, 4-vinylpyridine, N-vinylpyrrolidone, 2,4,6-triallyloxy-1,3,5-triazine, 1,4-cyclohexanedimethanol divinyl ether, benzyl methacrylate, phenyl methacrylate, benzyl acrylate, phenyl acrylate, isobornyl acrylate, glycidyl methacrylate, glycidyl acrylate, 2-naphthyl acrylate, trimethylsilyl acrylate, 2-phenoxyethyl acrylate, glucose acrylate, allyl phenyl ether, glyceryl acetone acrylate, glyceryl methacrylate, styrene acrylate, phenylethyl methacrylate, trifluoromethylphenyl acrylate, dicyclopentadiene acrylate, 1-acryloxyadamantane, o-phenylphenoxyethyl acrylate, diallyl isophthalate, triallyl 1,3,5-benzenetricarboxylate, paraphenylene The invention relates to diethylene glycol diacrylate, diethylene glycol diacrylate for phthalate, diethylene glycol diacrylate for isophthalate, diethylene glycol dimethacrylate for terephthalate, diethylene glycol dimethacrylate for phthalate, diethylene glycol dimethacrylate for isophthalate, dipropylene glycol diacrylate for terephthalate, dipropylene glycol diacrylate for phthalate, dipropylene glycol diacrylate for isophthalate, dibutylene glycol diacrylate for terephthalate, dibutylene glycol diacrylate for phthalate, dibutylene glycol diacrylate for isophthalate, cyclohexanedimethanol ester, cyclohexanedimethanol dimethacrylate, bisphenol A glyceride, N-hydroxysuccinimide acrylate, pyrrole acrylate, and thiophene acrylate, and further preferably one or more of cyclohexanedimethanol dimethacrylate, bisphenol A glyceride, diethylene glycol diacrylate for isophthalate, and methacrylate acetone glyceride.

[0011] The thiol-containing rigid compound is selected from one of the following substances or a mixture thereof: 2,6-naphthyldithiol, 4,4'-dithioldiphenyl ether, 4,4'-thiodiphenylthiol, dithiolthiadiazole, tetramercaptobenzene, biphenyl-4,4'-dithiol, 1,3,5-benzenetrithiol, trimercapto-s-triazine, 2,7-naphthyldithiol, 1,5-dimercaptonaphthalene, 2,2'-dimercaptobiphenyl, 2,5-dimercaptobenzene, 4,4'-dimercaptostilbene, 2,2'-dimercaptobipyrrol, 2,5-dimercaptopyrazole, dimercaptoacetophenone, 2,6-dimercaptothiophene, 3,5-dimercapto-1,2,4-triazacyclic ring, dimercaptosilane, 2,6-dimercaptopyridine, and one or more of tetramercaptobenzene and 1,3,5-benzenetrithiol are further preferred.

[0012] The photoinitiator is selected from one of the following substances or a mixture thereof: benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenylpropanone, benzoin ethyl ether, dibenzoyl, benzophenone, methyl o-benzoyl, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2-isopropyl-thioxanthen-9-one, 4-phenylbenzophenone, methyl A-oxyphenylacetate, 2-hydroxy-2-methylphenylpropane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2,2-dimethoxyphenylacetophenone. Further preferred is one or more of 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone and 2-hydroxy-2-methylphenylpropane-1-one.

[0013] The organic solvent is selected from one of the following substances or a mixture thereof: acetone, propylene glycol methyl ether acetate, acetonitrile, tetrahydrofuran, toluene, dimethylformamide, dimethyl sulfoxide, and acetone and propylene glycol methyl ether acetate are more preferred.

[0014] The organic solvent is a selective component. When the components of the nanoimprint photoresist meet the requirements of inkjet and imprinting or the addition of the organic solvent will affect the final imprinting effect, the organic solvent may not be added.

[0015] The inkjet printing method of the nanoimprint photoresist of the present invention comprises the following steps:

[0016] Step 1: Mix a rigid monomer containing a double bond, a rigid compound containing a thiol group, a photoinitiator and an organic solvent, stir and mix them evenly under light-proof conditions, and obtain a nanoimprint photoresist after filtering.

[0017] Step 2: Perform adhesion enhancement treatment on the silicon wafer. The specific steps are as follows:

[0018] Drop 0.2~1 mL of the thickener on the vacuum-adsorbed silicon wafer in the spin coater. After the spin coating is completed, transfer the silicon wafer with the thickener to a hot plate for baking. After baking, take it out and cool it to room temperature for use. The silicon wafer after this step of thickening treatment is collectively referred to as the substrate.

[0019] Step 3: Inject 1-2 mL of the nanoimprint photoresist obtained in step 1 into the ink sac of the inkjet printer cartridge, then connect the ink cartridge to the inkjet printer interface, set the program to set the required inkjet pattern as a droplet array, align the print head with the substrate through the display screen, and after the inkjet printer runs for 5-300 s, the corresponding inkjet pattern can be obtained on the substrate.

[0020] Step 4: Transfer the substrate with the inkjet pattern obtained in step 3 to the vacuum chuck of the nanoimprint lithography machine, turn on the air pump to fix the substrate, and align the substrate with the bottom of the quartz mold, adjust the imprint voltage of the nanoimprint lithography machine at 1~10 volts, so that the mold moves down and contacts the droplet array on the substrate. After the nanoimprint photoresist fully fills the gap in the mold, turn on ultraviolet light for curing. After curing is completed, turn off the ultraviolet lamp and detach from the mold.

[0021] In step 1, the filter used for filtration has a pore size of 0.2 to 2 μm.

[0022] In step 1, the viscosity of the obtained nanoimprint photoresist is 1 to 20 centipoise, preferably 7 to 10 centipoise.

[0023] In step 2, the tackifier is a mixture of 3-trimethoxysilane propyl acrylate, propylene glycol methyl ether acetate and acetone, and the mass ratio of the three is 0.5~2 g: 0.5~1.5 g: 0.1~0.5 g.

[0024] In step 2, set the spin coater speed to 1000-3000 rpm and the spin coating time to 30-90 s.

[0025] In step 2, the baking temperature is 50-150°C, and the baking time is 1-2 min.

[0026] In step 3, the area of ​​inkjet printing is preferably 1 to 50 mm 2 , further preferably 1~25 mm 2; The inkjet voltage is preferably 10~40 volts, and more preferably 20~30 volts; the inkjet air pressure is preferably 0~40 pounds force per square inch, and more preferably 1~10 pounds force per square inch; the inkjet frequency is preferably 500~7000 Hz, and more preferably 3000~5000 Hz; the inkjet droplet diameter is preferably 10~50 μm, and more preferably 20~40 μm; the inkjet droplet point spacing is preferably 10~100 μm, and more preferably 70~100 μm; the nozzle temperature is preferably 20~60°C, and more preferably 20~30°C; the substrate temperature is preferably 20~90°C, and more preferably 20~30°C.

[0027] In step 4, the UV light power is 50-110 mW, and the curing time is 10-30 s.

[0028] The preparation of the test sample and the characterization of the mechanical properties of the nanoimprint photoresist of the present invention include the following steps:

[0029] (1) Take 0.5-1 mL of the prepared nanoimprint photoresist and inject it through a filter with a pore size of 0.2 μm into a square hollow area with a side length of 40-80 mm and a thickness of 0.1-0.4 mm.

[0030] (2) Move the entire square hollow area containing the nanoimprint photoresist to the bottom of the light source of the nanoimprint lithography machine, adjust the program voltage to 1-10V so that the blank quartz on the nanoimprint lithography machine is completely in contact with the nanoimprint photoresist in the square hollow area and remove the bubbles, turn on the ultraviolet light for curing, the power of the ultraviolet light is 50-110mW, and the irradiation time is 60-300s. After the curing is completed, turn off the ultraviolet lamp and detach from the quartz, and then carefully peel off the cured nanoimprint photoresist.

[0031] (3) Using a 2 mm × 35 mm type 4 cutter that complies with the GB / T 528-2009 standard, the nanoimprint photoresist cured in the above step is cut to obtain a standard dumbbell-shaped specimen.

[0032] (4) The above standard dumbbell-shaped specimens were used to carry out stress-strain tests in a universal tensile machine at a tensile rate of 5 mm / min.

[0033] The Young's modulus of the nanoimprint photoresist of the present invention is 0.001-1.5 GPa, and more preferably 0.8-1.2 GPa; the fracture strength of the nanoimprint photoresist is 0.5-35 MPa, and more preferably 10-35 MPa; the fracture strain of the nanoimprint photoresist is 1-50%, and more preferably 5-15%.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0035] (1) Low viscosity at room temperature (liquid phase, 7-10 centipoise), which allows for rapid dispensing through an inkjet print head and subsequent rapid curing and imprinting on a nanoimprint lithography machine (10 s), effectively solving the compatibility issue between inkjet printing technology and nanoimprint technology to a certain extent.

[0036] (2) After curing, it leaves little adhesion to the mold, can be well released from the mask and preferably adheres to the substrate, which can avoid pattern defects and repeated defects in subsequent imprinting.

[0037] (3) Anti-oxidation and polymerization inhibition ensure that the nanoimprint photoresist is completely cured, reduce microstructure defects, and improve graphic accuracy.

[0038] (4) High mechanical strength, ensuring the replication accuracy of the pattern during the curing process and the high resolution of the embossed pattern (≤50nm). BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 A representative inkjet-printed pattern of nanoimprint photoresist PR-2 is shown.

[0040] Figure 2 Shown is the apparatus for preparing nanoimprint photoresist (a) and a diagram of a standard dumbbell-shaped spline (b).

[0041] Figure 3 The stress-strain curve graph of nanoimprint photoresist PR-1 is shown.

[0042] Figure 4 The stress-strain curve graph of nanoimprint photoresist PR-2 is shown.

[0043] Figure 5 The stress-strain curve graph of nanoimprint photoresist PR-3 is shown.

[0044] Figure 6 The imprint pattern of nanoimprint photoresist PR-1 is shown.

[0045] Figure 7 The imprint pattern of nanoimprint resist PR-2 is shown. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The implementation conditions used in the examples can be further adjusted according to the circumstances, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0047] Examples 1 to 7 are a formulation and preparation of a nanoimprint photoresist with high mechanical strength and high resolution.

[0048] Embodiment 1:

[0049] In this embodiment, a nanoimprint photoresist with high mechanical strength and high resolution (nanoimprint photoresist PR-1) is obtained by uniformly mixing the components according to formula 1. The formula is shown in Table 1 below.

[0050]

[0051] Embodiment 2:

[0052] In this embodiment, a nanoimprint photoresist with high mechanical strength and high resolution (nanoimprint photoresist PR-2) is obtained by uniformly mixing the components according to formula 2. The formula is shown in Table 2 below.

[0053]

[0054] Embodiment 3:

[0055] In this embodiment, a nanoimprint photoresist with high mechanical strength and high resolution (nanoimprint photoresist PR-3) is obtained by uniformly mixing the components according to formula 3. The formula is shown in Table 3 below.

[0056]

[0057] Embodiment 4:

[0058] The difference between Example 4 and Example 2 is that 1,4-cyclohexanedimethanol divinyl ether is used in the components to replace cyclohexanedimethanol dimethacrylate, and benzyl methacrylate is used to replace methacrylate acetone glycerol ester. The formula after the replacement is called nanoimprint photoresist PR-4.

[0059] Embodiment 5:

[0060] The difference between Example 5 and Example 2 is that divinylbenzene is used in the components to replace cyclohexanedimethanol dimethacrylate and diethylene glycol isophthalate diacrylate, and the formula after the replacement is called nanoimprint photoresist PR-5.

[0061] Embodiment 6:

[0062] The difference between Example 6 and Example 2 is that diallyl isophthalate is used in the components to replace cyclohexanedimethanol dimethacrylate and diethylene glycol isophthalate diacrylate, and the formula after the replacement is called nanoimprint photoresist PR-6.

[0063] Embodiment 7:

[0064] The difference between Example 7 and Example 2 is that 2,4,6-triallyloxy-1,3,5-triazine is used in the components to replace cyclohexanedimethanol dimethacrylate and isophthalic acid diethylene glycol diacrylate, and the formula after the replacement is called nanoimprint photoresist PR-7.

[0065] Embodiment 8:

[0066] After the nanoimprint photoresists were prepared according to the respective formulations in Examples 1 to 7, the viscosity was tested using a rotational viscometer. The volume of the nanoimprint photoresists of the respective formulations was 6 to 7 mL, and the parameters of the viscometer were set as follows: the rotor type was 18#, the rotation speed was 90 rpm, the test temperature was 25°C, the test time was 30 s, and the viscosity value was recorded after the test.

[0067]

[0068] Embodiment 9:

[0069] After the nanoimprint photoresists are prepared according to the respective recipes in Examples 1 to 7, they are used according to the following steps:

[0070] (1) Clean the substrate, ultrasonicate the silicon wafer in acetone, isopropanol, and water for 10 min, and then treat it with oxygen plasma for 2 min.

[0071] (2) The above silicon wafer is subjected to a viscosity-enhancing treatment. First, a viscosity-enhancing agent is prepared by preparing a mixture of 3-trimethoxysilane propyl acrylate, propylene glycol methyl ether acetate and acetone in a mass ratio of 1 g: 0.75 g: 0.1 g to obtain a viscosity-enhancing agent. 0.5 mL of the viscosity-enhancing agent is dropped onto the silicon wafer that has been adsorbed and fixed in step (1) in a spin coater. The spin coater parameters are set to a speed of 2000 rpm and a spin coating time of 45 s. After the spin coating is completed, the silicon wafer coated with the viscosity-enhancing agent is removed and transferred to a hot plate for baking at a temperature of 120°C for 2 min. After the baking is completed, the treated silicon wafer is removed and cooled to room temperature for standby use (the silicon wafer after the viscosity-enhancing treatment is subsequently referred to as the substrate).

[0072] (3) 1.5 mL of the prepared nanoimprint photoresist was filtered and injected into the ink sac of the inkjet printer cartridge. The pore size of the filter was 0.2 μm. Then, the ink cartridge containing the nanoimprint photoresist was connected to the inkjet printer interface. The program set the inkjet pattern to droplet array and the inkjet printing area to 2 mm. 2 , the inkjet voltage is 25 volts, the inkjet pressure is 1 pound force / square inch, the inkjet frequency is 5000 Hz, the inkjet point spacing is 80 μm, the nozzle temperature is 25°C, the substrate temperature is 25°C, and the nozzle is aligned with the center of the substrate through the operating display. After the inkjet printer runs for 30 seconds, an area of ​​2 mm2 can be obtained on the substrate. 2The inkjet pattern was then observed under a microscope.

[0073] (4) The substrate with the inkjet pattern is transferred to the vacuum chuck of the nanoimprint lithography machine and fixed. The imprint voltage of the nanoimprint lithography machine is adjusted to 6 volts for alignment, so that the quartz mold directly above the substrate moves down and contacts the droplet array on the substrate. After the nanoimprint photoresist fully fills the mold gap, ultraviolet light is turned on for curing. The power of the ultraviolet light is 110 mW, and the irradiation time is 10 s or 30 s. After the curing is completed, the ultraviolet lamp is turned off and the "mold release" button is clicked to release the mold.

[0074] (5) Observe the effect of inkjet curing under a microscope, including the residual liquid film of nanoimprint photoresist after ultraviolet light irradiation and the residual of cured nanoimprint photoresist on the mold.

[0075]

[0076] (6) As a representative example, the inkjet pattern prepared in Example 2 is as follows Figure 1 As shown, the imprint patterns of the nanoimprint photoresists of the representative embodiments 1 and 2 are respectively as shown in Figure 6 and Figure 7 shown.

[0077] The purpose of this embodiment is to illustrate that

[0078] ①Observe the inkjet pattern through a microscope ( Figure 1 ), the viscosity of the nanoimprint photoresist is 7~10 centipoise, the inkjet voltage is 25 volts, the inkjet pressure is 1 pound per square inch, the inkjet frequency is 5000 Hz, the inkjet droplet diameter is 40 μm, the inkjet droplet point spacing is 80 μm, the nozzle temperature is 25°C, and the substrate temperature is 25°C. At this time, a relatively uniform droplet array can be inkjet printed.

[0079] ②Nanoimprint photoresist can be completely cured (without liquid film residue) within a very short exposure time, which is attributed to the rapidity of free radical polymerization reaction during the polymerization process and the antioxidant inhibition effect provided by thiol.

[0080] ③Acrylate double bond components contained in the tackifier may participate in the photocuring process of the nanoimprint photoresist. Therefore, during the demolding process, the nanoimprint photoresist will selectively remain on the substrate side and almost no residue will be left on the mold, thus ensuring the cleanliness of the mold.

[0081] Embodiment 10:

[0082] After the nanoimprint photoresists were prepared according to the respective formulas in Examples 1 to 3, standard dumbbell-shaped specimens of the nanoimprint photoresists were prepared according to the following steps for mechanical property testing:

[0083] (1) Take 0.6 mL of the nanoimprint photoresist prepared according to the respective recipes of Examples 1 to 3, pass it through a filter with a pore size of 0.2 μm, and inject it into a Figure 2 In the square hollow area with a side length of 40 mm and a thickness of 200 μm shown in a, Figure 2 The silicon wafer in a has been subjected to adhesion enhancement treatment according to step (2) in Example 9.

[0084] (2) Move the square hollow device containing nanoimprint photoresist into the position directly below the light source of the nanoimprint lithography machine, adjust the program voltage of the nanoimprint lithography machine to 6 volts, so that the blank quartz on the nanoimprint lithography machine moves down and fits closely with the nanoimprint photoresist liquid in the square hollow and fully removes bubbles, turn on ultraviolet light for curing, the power of ultraviolet light is 110 mW, and the irradiation time is 300 s. After curing is completed, turn off the ultraviolet light, click the "mold release" button to detach from the quartz, and then carefully peel off the nanoimprint photoresist.

[0085] (3) Using a 2 mm × 35 mm type 4 cutter that complies with the GB / T 528-2009 standard, the nanoimprint photoresist prepared in the above step is cut to obtain the following: Figure 2 b shows the standard dumbbell spline.

[0086] (4) The stress-strain test was carried out on a universal tensile machine using the above standard dumbbell-shaped specimens at a stretching rate of 5 mm / min. The stress-strain test of each formulation was conducted at least three times.

[0087] The stress-strain test results of the standard dumbbell-shaped specimens prepared in Examples 1 to 3 are as follows: Figure 3~Figure 5 As shown, since the photocuring effect of the nanoimprint photoresists of Examples 4 to 7 is poor, no further research on the mechanical properties was conducted.

[0088]

[0089] Embodiment 11:

[0090] The purpose of this example is to illustrate the influence of the organic solvent in the nanoimprint photoresist formulation on the mechanical properties of the nanoimprint photoresist.

[0091] As shown in Table 6, Figure 3As shown in the figure, when an organic solvent is added as a viscosity modifier in the formulation of nanoimprint photoresist, the addition of a small amount of solvent will result in the nanoimprint photoresist PR-1 having only extremely low mechanical strength. This may be because the small solvent molecules interfere with and destroy the original cross-linking points, and at the same time weaken the interaction between the chains after penetrating into the polymer chains, thereby reducing the tightness of the cross-linking network. As the cross-linking structure relaxes, the rigidity of the material decreases significantly, resulting in a sharp deterioration in mechanical properties.

[0092] Embodiment 12:

[0093] The purpose of this example is to illustrate the effect of changing the amount of photoinitiator in the nanoimprint photoresist formulation on the mechanical properties of the nanoimprint photoresist.

[0094] Analysis Table 6 Figure 4 and Figure 5 When the amount of photoinitiator used in nanoimprint photoresist PR-3 is increased to twice that of PR-2, the Young's modulus and fracture strength of PR-3 are reduced to about half of those of PR-2 at the same exposure time. This may be due to the excessive amount of photoinitiator, which leads to a too fast cross-linking reaction rate, resulting in an uneven cross-linking process and the formation of an irregular cross-linking network structure. This uneven cross-linking network affects the mechanical properties of the material, which in turn leads to a significant decrease in its Young's modulus and fracture strength.

[0095] Embodiment 13:

[0096] The purpose of this example is to illustrate the importance of high mechanical strength of nanoimprint photoresist for imprinting high-resolution nanostructures.

[0097] Analysis Table 6 Figure 3 and Figure 4 , comparing nanoimprint photoresist PR-1 with nanoimprint photoresist PR-2, the fracture strain of PR-1 (8.9±0.300%) is higher than that of PR-2 (6.9±0.0109%), and the Young's modulus and fracture strength of PR-1 are much lower than those of PR-2. In comparison, the imprinted "grating" of nanoimprint photoresist PR-1 has more obvious defects ( Figure 6 ). This indicates that when there is a similar fracture strain, the higher Young's modulus (>1.1 GPa) and fracture strength (>30 MPa) in the nanoimprint photoresist PR-2 may be the key to ensure high resolution of imprinting less than 50 nm ( Figure 7 ).

[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A nanoimprint photoresist with high mechanical strength and high resolution, characterized in that The raw materials are composed of the following by mass percentage: 50 wt%~95 wt% of a rigid monomer containing a double bond, 0 wt%~20 wt% of a rigid compound containing a thiol group, 1 wt%~20 wt% of a photoinitiator, and 0 wt%~20 wt% of an organic solvent.

2. The nanoimprint photoresist according to claim 1, characterized in that The raw materials are composed of the following by mass percentage: 80 wt%~95 wt% of a rigid monomer containing a double bond, 1 wt%~10 wt% of a rigid compound containing a thiol group, 1 wt%~10 wt% of a photoinitiator, and 0 wt%~15 wt% of an organic solvent.

3. The nanoimprint photoresist according to claim 1, characterized in that: The double bond-containing rigid monomer is selected from one of the following substances or a mixture thereof: styrene, divinylbenzene, 4-vinylpyridine, N-vinylpyrrolidone, 2,4,6-triallyloxy-1,3,5-triazine, 1,4-cyclohexanedimethanol divinyl ether, benzyl methacrylate, phenyl methacrylate, benzyl acrylate, phenyl acrylate, isobornyl acrylate, glycidyl methacrylate, glycidyl acrylate, 2-naphthyl acrylate, trimethylsilyl acrylate, 2-phenoxyethyl acrylate, glucose acrylate, allyl phenyl ether, acetone glycerol acrylate, methacrylate acetone glycerol ester, styrene acrylate, phenylethyl methacrylate, trifluoromethylphenyl acrylate, dicyclopentadiene acrylate, 1-acryloyloxyadamantane, o-phenylphenoxyethyl acrylate Acid ester, diallyl isophthalate, triallyl 1,3,5-benzenetricarboxylate, diethylene glycol terephthalate diacrylate, diethylene glycol phthalate diacrylate, diethylene glycol isophthalate diacrylate, diethylene glycol terephthalate dimethacrylate, diethylene glycol phthalate dimethacrylate, diethylene glycol isophthalate dimethacrylate, dipropylene glycol terephthalate diacrylate, dipropylene glycol phthalate diacrylate, dipropylene glycol isophthalate diacrylate, dibutylene terephthalate diacrylate, dibutylene phthalate diacrylate, dibutylene isophthalate diacrylate, cyclohexanedimethanol ester, cyclohexanedimethanol dimethacrylate, bisphenol A glyceride, N-hydroxysuccinimide acrylate, pyrrole acrylate, thiophene acrylate.

4. The nanoimprint photoresist according to claim 1, characterized in that: The rigid compound containing a thiol group is selected from one of the following substances or a mixture thereof: 2,6-naphthyl dithiol, 4,4'-dithiol diphenyl ether, 4,4'-thiodiphenylthiol, dithiol thiadiazole, tetramercaptobenzene, biphenyl-4,4'-dithiol, 1,3,5-benzenetrithiol, trimercapto-s-triazine, 2,7-naphthyl dithiol, 1,5-dimercaptonaphthalene, 2,2'-dimercaptobiphenyl, 2,5-dimercaptobenzene, 4,4'-dimercaptostilbene, 2,2'-dimercaptobipyrrol, 2,5-dimercaptopyrazole, dimercaptoacetophenone, 2,6-dimercaptothiophene, 3,5-dimercapto-1,2,4-triazacyclic ring, dimercaptosilane, and 2,6-dimercaptopyridine.

5. The nanoimprint photoresist according to claim 1, characterized in that: The mercapto-containing rigid compound is selected from one or more of tetramercaptobenzene and 1,3,5-benzenetrithiol.

6. The nanoimprint photoresist according to claim 1, characterized in that: The photoinitiator is selected from one of the following substances or a mixture thereof: benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenylpropanone, benzoin ethyl ether, dibenzoyl, benzophenone, methyl o-benzoyl, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2-isopropyl-thioxanthen-9-one, 4-phenylbenzophenone, A-oxyphenylacetic acid methyl ester, 2-hydroxy-2-methylphenylpropane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, and 2,2-dimethoxyphenylacetophenone.

7. The inkjet printing method of the nanoimprint photoresist according to any one of claims 1 to 6, characterized in that The steps include: Step 1: Mix a rigid monomer containing a double bond, a rigid compound containing a thiol group, a photoinitiator and an organic solvent, stir and mix them evenly under light-proof conditions, and obtain a nanoimprint photoresist after filtering; Step 2: Perform adhesion enhancement treatment on the silicon wafer; Step 3: Inject 1-2 mL of the nanoimprint photoresist obtained in step 1 into the ink sac of the inkjet printer cartridge, then connect the inkjet printer cartridge to the interface of the inkjet printer, set the required inkjet pattern to a droplet array through the program, align the print head with the substrate through the display screen, and after the inkjet printer runs for 5-300 s, the corresponding inkjet pattern can be obtained on the substrate; Step 4: Transfer the substrate with the inkjet pattern obtained in step 3 to the vacuum chuck of the nanoimprint lithography machine, turn on the air pump to fix the substrate, and align the substrate with the bottom of the quartz mold, adjust the imprint voltage of the nanoimprint lithography machine at 1~10 volts, so that the mold moves down and contacts the droplet array on the substrate. After the nanoimprint photoresist fully fills the gap in the mold, turn on ultraviolet light for curing. After curing is completed, turn off the ultraviolet lamp and detach from the mold.

8. The inkjet printing method according to claim 7, characterized in that: In step 1, the viscosity of the obtained nanoimprint photoresist is 1-20 centipoise.

9. The inkjet printing method according to claim 7, characterized in that: In step 2, the viscosity increasing treatment comprises the following steps: Drop 0.2-1 mL of the thickener on the vacuum-adsorbed silicon wafer in the spin coater. After the spin coating is completed, transfer the silicon wafer coated with the thickener to a hot plate for baking. After the baking is completed, take it out and cool it to room temperature for later use. The tackifier is a mixture of 3-trimethoxysilane propyl acrylate, propylene glycol methyl ether acetate and acetone.

10. The inkjet printing method according to claim 7, characterized in that: In step 3, the area of ​​inkjet printing is 1~50 mm 2 , the inkjet voltage is 10~40 volts, the inkjet air pressure is 0~40 lbf / square inch, the inkjet frequency is 500~7000 Hz, the inkjet droplet diameter is 10~50 μm, the inkjet droplet point spacing is 10~100 μm, the nozzle temperature is 20~60°C, and the substrate temperature is 20~90°C.

Citation Information

Patent Citations

  • Curable composition, color filter and manufacturing method thereof

    CN101154039A

  • Sulfydryl-containing low polysiloxane compound, ultraviolet photoresist composition thereof, and impressing process

    CN102174059A

  • Super-hydrophobic chip for enrichment and condensation of molecules as well as preparation method and application thereof

    CN106093004A

  • Radiation curing inkjet ink composition, inkjet recording method, recorded matter, ink set for inkjet recording, ink cartridge, and inkjet recording device

    JP2009249561A

  • Photosensitive resin composition, and cured film of the same

    JP2024091503A

Cited By

  • Ultraviolet curing nanoimprint photoresist with semi-interpenetrating network structure and preparation method of ultraviolet curing nanoimprint photoresist

    CN121559814A

  • An ultraviolet-cured nanoimprint photoresist with a semi-interpenetrating network structure and a preparation method thereof

    CN121559814B

  • Nanoimprint lithography resist having high mechanical strength and enabling high resolution and inkjet printing method therefor

    WO2026158133A1